Innovative wearable technology for continuous echocardiographic monitoring: first-in-neonate case report - Wang, Yan; Wu, Gangjun; Song, Jianqiang; Song, Haibo; Chu, Qinjun (Frontiers in Pediatrics, 2025)
Neonates in the early stage are in the transition from fetal to adult circulation, accompanied by complex hemodynamic changes, which are prone to aggravate the condition of the circulatory system during the perioperative period. Here, we present a case of a 3-day-old neonate with upper gastrointestinal bleeding caused by multiple esophageal and gastric ulcers. To achieve accurate circulation management, we utilized a novel wearable ultrasound device for non—invasive, continuous echocardiographic monitoring throughout general anesthesia gastroscopy and postoperative NICU care. The case demonstrates the feasibility of continuous echocardiographic monitoring in neonates and offers new ideas for circulatory monitoring and management in critical neonates.